2015
DOI: 10.1261/rna.048298.114
|View full text |Cite
|
Sign up to set email alerts
|

oskar RNA plays multiple noncoding roles to support oogenesis and maintain integrity of the germline/soma distinction

Abstract: The Drosophila oskar (osk) mRNA is unusual in that it has both coding and noncoding functions. As an mRNA, osk encodes a protein required for embryonic patterning and germ cell formation. Independent of that function, the absence of osk mRNA disrupts formation of the karyosome and blocks progression through oogenesis. Here we show that loss of osk mRNA also affects the distribution of regulatory proteins, relaxing their association with large RNPs within the germline, and allowing them to accumulate in the som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 35 publications
3
71
0
Order By: Relevance
“…The comparison of egg-laying by females lacking endogenous osk RNA with those expressing osk transgenes that disrupt some or all the BREs showed that the mutation of any BRE reduces egg-laying to some extent, with the strongest effect observed when all BREs are lost. The reduction in egg-laying appears to be due to disruption of the non-coding function of osk RNA (Kanke et al, 2015).…”
Section: Oskarmentioning
confidence: 99%
See 4 more Smart Citations
“…The comparison of egg-laying by females lacking endogenous osk RNA with those expressing osk transgenes that disrupt some or all the BREs showed that the mutation of any BRE reduces egg-laying to some extent, with the strongest effect observed when all BREs are lost. The reduction in egg-laying appears to be due to disruption of the non-coding function of osk RNA (Kanke et al, 2015).…”
Section: Oskarmentioning
confidence: 99%
“…A more recent study showed, remarkably, that the expression of a transgenic 191-nucleotide segment of the osk 3′UTR is sufficient to rescue the oogenesis arrest of osk RNA null oocytes, as long as the RNA is fused to a stem-loop structure that promotes its dyneindependent import into the oocyte (Kanke et al, 2015). It was further shown that mutations in the osk 3′UTR that abolish binding of the translational regulator Bruno (Bru; Aret -FlyBase) to Bru response elements (BREs) in osk also affect egg laying (Kanke et al, 2015).…”
Section: Oskarmentioning
confidence: 99%
See 3 more Smart Citations